Brain Based Learning Framework for Beginner Indonesian Language Acquisition: Kerangka Pembelajaran Berbasis Otak untuk Pemerolehan Bahasa Indonesia Tingkat Pemula - Nazwa, Nurul Fara; Syamsuyurnita, Syamsuyurnita (Academia Open, 2026)
General Background: Indonesian as a Foreign Language (BIPA) instruction is increasingly vital in the Southeast Asian educational landscape, necessitating adaptive pedagogical strategies to facilitate cross-cultural communication. Specific Background: Beginner BIPA learners in Thailand often face significant challenges, including limited linguistic exposure, high cognitive demands, and anxiety, which hinder their initial language acquisition. Knowledge Gap: While current BIPA research prioritizes technological tools, there is a deficiency in empirical studies applying neuro-pedagogical frameworks—specifically Brain-Based Learning (BBL)—to optimize the receptive–pre-productive stages of language development. Aims: This study examined the application of the BBL model on basic Indonesian vocabulary mastery as a foundation for early speaking readiness among beginner BIPA learners. Results: Using a mixed-methods sequential explanatory design, the study revealed a statistically significant improvement in vocabulary mastery (t = 2.21, p = 0.040), with mean scores rising from 76.32 to 86.32. Novelty: This research provides empirical evidence that BBL-driven instruction—emphasizing multisensory stimulation and positive emotional engagement—effectively constructs cognitive-linguistic foundations for novice learners. Implications: Brain-Based Learning offers a meaningful instructional framework for beginner-level BIPA learners by strengthening receptive–pre-productive vocabulary foundations as vital preparation for subsequent speaking development. Highlights The Brain-Based Learning model significantly improves vocabulary mastery for beginner-level foreign language learners. Instructional designs incorporating multisensory stimulation and positive emotional management reduce language learning anxiety and increase learner participation. Systematic vocabulary acquisition at the receptive–pre-productive stage serves as a crucial cognitive foundation for future productive speaking proficiency. Keywords Brain-Based Learning; BIPA; Indonesian Vocabulary Mastery; Receptive–Pre-Productive Stage; Mixed-Methods